Un grand domaine aristocratique de la cité des Viromanduens : la villa de La Mare aux Canards (Noyon, Oise) - Marjolaine de Muylder; Guillaume Aubazac; Frédéric Broes; Stéphane Dubois; Bastien Dubuis; Caroline Font; Alexia Morel (Gallia)
Situated in the town of Noyon (Oise), the Mare aux Canards villa is located less than one kilometer southwest of the road linking Amiens-Samarobriva to Soissons-Augusta Suessionum and the antique Viromanduan secondary urban area, Noviomagus, this road crosses. This estate has a 12 hectare area and follows a « multiple lined pavilions » villa scheme. The main question is about the status of this villa, which stands out by its size and its general structure. The pars rustica excavation yielded a very rich architecture and furniture that gives an aristocratic feature to the building. Its function don’t seem to be devoted to traditional farming, but could be closer to business and commercial trade.